Capabilities of BIOMASS Three-Baseline PolInSAR Mode for the Characterization of Tropical Forests - Yanzhou Xie; Laurent Ferro-Famil; Yue Huang; Thuy Le Toan; Jianjun Zhu; Haiqiang Fu; Peng Shen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
As the 7th Earth Explorer Mission within the ESA Earth Observation Program, BIOMASS will be the first spaceborne P-band polarimetric interferometric SAR (PolInSAR) mission, dedicated to global forest remote sensing. Compared with airborne PolInSAR, BIOMASS PolInSAR faces several intrinsic limitations, including the reduced number of baselines, low bandwidth of 6 MHz, and the 3-day repeat-pass acquisition mode. In this study, the capabilities of three-baseline PolInSAR in BIOMASS configuration and the spaceborne system-induced impacts are systematically evaluated. First, the BIOMASS data were simulated using the airborne P-band SAR acquisitions collected over two different tropical forests in Paracou, French Guiana, and Mondah, Gabon. Second, the forest height was retrieved using a three-baseline algorithm based on polarimetric coherence optimization with multi-baseline joint diagonalization. Finally, the impacts of spaceborne PolInSAR were quantified and analyzed. The results show that the performance of PolInSAR inversion in the spaceborne configuration decreases compared to that of the original airborne data. However, the three-baseline method still yields acceptable results, with a root-mean-square error ranging from 4.92 to 6.07 m and a correlation coefficient (R2) from 0.32 to 0.85, within hectare-scale forest height statistics. This study demonstrates that the limited bandwidth of BIOMASS has a certain impact on refined forest structure parameter retrieval, while the three-baseline PolInSAR method remains effective for large-scale forest mapping, with accuracy meeting the design requirements of the BIOMASS mission.